(untitled) - Nasar, Sylvia (New York, N.Y., 1998)
In this biography, Sylvia Nasar re-creates the life of a mathematical genius whose brilliant career was cut short by schizophrenia and who, after three decades of devastating mental illness, miraculously recovered and was honored with a Nobel Prize. A Beautiful Mind traces the meteoric rise of John Forbes Nash, Jr., from his lonely childhood in West Virginia to his student years at Princeton, where he encountered Albert Einstein, John von Neumann, and a host of other mathematical luminaries. At twenty-one, the handsome, ambitious, eccentric graduate student invented what would become the most influential theory of rational human behavior in modern social science. Nash's contribution to game theory would ultimately revolutionize the field of economics. At thirty, Nash was poised to take his dreamed-of place in the pantheon of history's greatest mathematicians. Then Nash suffered a catastrophic mental breakdown.
Keywords: Toán học,Mathematicians; Tiểu sử,Biography; Hoa Kỳ,United States